Economic Dynamics and Sustainable Forestry: Pathways to Net Zero Emissions in Indonesia - Erwinsyah (Journal of Developing Economies, 2026)
Objective: The study examines the economic drivers and sustainability issues of Indonesia’s forestry sector, which are crucial for national economic growth, export revenues, and employment opportunities. The forest-based industry promotes monetary stability and poverty reduction, although it also produces considerable environmental externalities, particularly carbon emissions from deforestation and land-use changes. Design/Methods/Approach: This study uses a novel simultaneous-equations econometric model to analyze key factors influencing deforestation, including GDP growth, commodity prices, policy incentives, sustainable practices, and forest land availability, thereby capturing complex bidirectional relationships and feedback effects over the period 2000–2023. Findings: Results indicate that while economic growth and stable commodity prices reduce deforestation, high land management costs hinder sustainable practices. Given the limited influence of policy incentives, more complex financial and governance frameworks were required. Originality/Value: The study emphasizes the significance of Indonesia’s forest management strategies in the context of global environmental commitments and market demands for deforestation-free products, providing a nuanced econometric understanding of these interdependencies. Practical/Policy implications: Integrated forest management, financial support systems, legal reforms, and collaboration with international stakeholders are some of the recommendations that have been made to reconcile the goals of economic growth with environmentally sustainable development.